2000
DOI: 10.1515/jpm.2000.056
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maternal weight gain on infant birth weight

Abstract: The results confirmed that excessive maternal weight gain in pregnancy (> 35 lbs), does result in higher birth weight infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
26
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 3 publications
(2 reference statements)
8
26
0
3
Order By: Relevance
“…In an earlier paper (Lagiou et al, in press), examining nonnutritional factors in relation to birth weight, we found, as others have (Abrams & Selvin, 1995;Zhou & Olsen, 1997;Thorsdottir & Birgisdottir, 1998;Shapiro et al, 2000), that maternal weight gain is positively associated with birth weight. Among Caucasian women, an increase in maternal weight gain by 2 kg was associated with an increase of 37.1 g (standard error 13.2 g) in birth weight, after adjustment for possible confounding variables (Lagiou et al, in press).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In an earlier paper (Lagiou et al, in press), examining nonnutritional factors in relation to birth weight, we found, as others have (Abrams & Selvin, 1995;Zhou & Olsen, 1997;Thorsdottir & Birgisdottir, 1998;Shapiro et al, 2000), that maternal weight gain is positively associated with birth weight. Among Caucasian women, an increase in maternal weight gain by 2 kg was associated with an increase of 37.1 g (standard error 13.2 g) in birth weight, after adjustment for possible confounding variables (Lagiou et al, in press).…”
Section: Discussionsupporting
confidence: 80%
“…In contrast, smoking (England et al, 2001) and coffee consumption (Eskenazi et al, 1999) during pregnancy have been linked to lower birth weight. Although maternal weight gain has been consistently linked to birth weight (Abrams & Selvin, 1995;Zhou & Olsen, 1997;Thorsdottir & Birgisdottir, 1998;Shapiro et al, 2000;Lagiou et al, 2003), the relation of energy-generating nutrients with birth size after controlling for energy-intake has not been adequately investigated. Indeed, the sequence from maternal nutrition to maternal weight gain to birth weight is not sustained by available data, except under extreme nutritional deprivation (Susser, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The weight to gain during pregnancy in industrialized countries is an important factor associated with fetal growth. [2,3] Our study supports the hypothesis that, in this particular population, the nutritional status of the mother, as reflected by the body mass index and weight in late pregnancy, also plays a key role in fetal growth, role seeming more important than the genetic determinism of the mother reflected by maternal height. The description of parental income in our population shows a dominance of low-income professions.…”
Section: Discussionsupporting
confidence: 84%
“…It is also known that women whose BMI is in this range in their first trimester have smaller infants (by 170 g) than those with a higher BMI (> 25 kg/m 2 ). 21 In Note: DXA = dual-energy x-ray absorptiometry, BMC = bone mineral content. *Deficiency defined as plasma 25(OH)D less than 37.5 nmol/L.…”
Section: Discussionmentioning
confidence: 99%